Corrosion electrochemistry with a segmented array bipolar electrode. (10th April 2021) - Zhou, Yiqi; Stevens, Nicholas; Engelberg, Dirk Lars
Highlights: Application of bipolar electrochemistry provides access to the full range of anodic-to-cathodic polarisation behaviour. Potential and current distributions have been experimentally determined using a segmented array bipolar electrode. Comparison between bipolar electrochemistry and conventional 3-electrode polarisation tests. Measurements of pitting corrosion kinetics with bipolar electrochemistry. Abstract: Bipolar electrochemistry was applied to determine the full spectrum of anodic-to-cathodic polarisation behaviour of stainless steel. The potential and current distributions at the sample surface were determined using a segmented array bipolar electrode (BPE). The measured potential shows a quasi-linear gradient along the centre of the BPE, with the current following an exponential Butler–Volmer-type relationship. Bipolar electrochemistry is compared to conventional 3-electrode polarisation testing, allowing determination of the critical pitting potential, general corrosion rates and the cathodic current response. The application of bipolar electrochemistry is demonstrated via measurement of pit growth kinetics in ferritic stainless steel. Graphical abstract: Image, graphical abstract